1997
DOI: 10.1111/j.1749-6632.1997.tb51748.x
|View full text |Cite
|
Sign up to set email alerts
|

Heatstroke‐Induced Cerebral Ischemia and Neuronal Damage

Abstract: Experiments were carried out to ascertain whether the levels of brain monoamines and cytokines are involved in the heatstroke-induced cerebral ischemia and neuronal damage. Heatstroke was induced by exposing anesthetized rats to a high ambient temperature of 42 degrees C; the moment at which the mean arterial pressure began to decrease from its peak level was taken as the onset of heatstroke. It was found that, during the heatstroke-induced cerebral ischemia and neuronal damage, the extracellular concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
62
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 51 publications
4
62
1
2
Order By: Relevance
“…The plasma levels of TNF-a and IL-1b are shown to be well related to the severity of heatstroke (34,35). Indeed, increased levels of these cytokines are associated with heatstroke-induced arterial hypotension, cerebral ischemia, and neuronal damage (32,33; present results). Prior antagonism of ET A (present results) or IL-1b receptors (36,37) protects against heatstrokeinduced arterial hypotension, and cerebral ischemic damage and prolongs survival.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The plasma levels of TNF-a and IL-1b are shown to be well related to the severity of heatstroke (34,35). Indeed, increased levels of these cytokines are associated with heatstroke-induced arterial hypotension, cerebral ischemia, and neuronal damage (32,33; present results). Prior antagonism of ET A (present results) or IL-1b receptors (36,37) protects against heatstrokeinduced arterial hypotension, and cerebral ischemic damage and prolongs survival.…”
Section: Discussionmentioning
confidence: 48%
“…Our present and previous (32,33) results have shown that heatstroke induces systemic and central production of TNF-a and interleukin-1b (IL-1b ) in both rats and rabbits. The plasma levels of TNF-a and IL-1b are shown to be well related to the severity of heatstroke (34,35).…”
Section: Discussionmentioning
confidence: 97%
“…22,35,36) There is evidence that cerebral ischemia (due to arterial hypotension and intracranial hypertension) may be one of the major causes to induce further damage after heat stroke onset. 14,19,37) After heat stroke induction, the CBF is instantly drops from highest peak, and it is concomitant with significant increments of cerebral ischemia and injury indexes, as shown in Fig. 1.…”
Section: Disscusionmentioning
confidence: 98%
“…6,9,11,14,15) Various clinical and experimental investigations have shown that single doses of dexamethasone (DXM; exogenous glucocorticoids) or mannitol are extensively used in the treatment of cerebral ischemia and/or cerebral injury. [16][17][18] In the studies of heat stroke, pretreatment with DXM attenuated serum IL-1b levels and improved survival in heat stroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation